Analisa Bauran Pemasaran Terhadap Volume Penjualan (Studi Kasus Toko Pakaian Boysdontcry) - Sutardjo; Elly Setiadewi; wijaya, raden purwa galuh (Jurnal Teknologika, 2023)
Boysdontcry is a business engaged in fashion distros. Sales volume at Boysdontcry has decreased and increased, so researchers analyze whether the strategy implemented by Boysdontcry is right. Data analysis in this study uses quantitative analysis methods, namely by managing data presented in the form of frequency and percentage tables, in this study using simple regression analysis methods using statistical application software tools SPSS (Statistical Program for Social Science)). The validity test is used to measure the appropriateness or absence of a questionnaire and produce a valid value, namely the r value of the table r count. The overall reliability test of the question items from each variable can be used and can be distributed to all respondents, because each item shows valid and reliable results based on the results of constant value data of 1.394. Stating that the regression coefficient of 0.204 means that the marketing mix has a positive relationship with sales volume. Every 1 unit increase in the marketing marketing mix will affect the average sales volume increase of 0.204. Conversely, every decrease in sales volume will affect the average decrease in marketing mix by 0.204. Boysdontcry is a business engaged in fashion distros. Sales volume at Boysdontcry has decreased and increased, so researchers analyze whether the strategy implemented by Boysdontcry is right. Data analysis in this study uses quantitative analysis methods, namely by managing data presented in the form of frequency and percentage tables, in this study using simple regression analysis methods using statistical application software tools SPSS (Statistical Program for Social Science)). The validity test is used to measure the appropriateness or absence of a questionnaire and produce a valid value, namely the r value of the table r count. The overall reliability test of the question items from each variable can be used and can be distributed to all respondents, because each item shows valid and reliable results based on the results of constant value data of 1.394. Stating that the regression coefficient of 0.204 means that the marketing mix has a positive relationship with sales volume. Every 1 unit increase in the marketing marketing mix will affect the average sales volume increase of 0.204. Conversely, every decrease in sales volume will affect the average decrease in marketing mix by 0.204.